From the characteristics of the researcher to the conditions of the interpreterA methodological approach to the principles of scientific research and the results of the infallibility of consideration in the Qur’anic discourseFirst introduction - Prof.Dr.Emad Jabbar Kadhem (Journal of College of Education, 2024)
The principles of scientific research methodology have imposed on those who seek to open its locks characteristics and qualities that the researcher must possess on the one hand, and conditions that the interpreter must achieve on the other hand; To enter any world of the missionary system, the final: whether a discourse, a text, or what is above them in value and holiness, which is the Holy Quran, and these are qualities and conditions that took multiple titles and concepts in the circles of reception, such as reading, dissection and deconstruction sometimes, and analysis, interpretation and exegesis, or the fields of hermeneutics and methods of criticism at other times, so their secrets of revelation varied on the qualities of the researcher and interpreter themselves without a difference, as if they were one in the field of Quranic theory and scientific research, so they were internal and subjective, and external and acquired: psychological, mental, cognitive, cultural, etc., entrances and layers to clarify the intended semantic meaning.